Modernizing nature forestry and imperial eco-development 1800-1950 - Rajan, S. Ravi (Oxford historical monographs., 2006)
Professor Rajan explores the origins, institutionalisation and politics of the sciences and systems of knowledge underlying colonial framework of environmental management. He disagress with historigraphical and social scientific approaches arguing that it had cognitive, ideological and interventionalist traditions.